PERLINDUNGAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL KOMUNAL DI SULAWESI UTARA - Anis, Friend Henry; Ollij Anneke Kereh; Karel Yossi Umboh (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This research aims to determine and analyze the substance of the regulation of communal intellectual property rights in Indonesia and to determine and analyze the role of Regional Government in providing legal protection for communal intellectual property rights in North Sulawesi. The method used in this research is a normative legal research method which uses a statutory approach to examine the regulation of communal intellectual property rights and an empirical method to determine the role of Regional Government in providing protection for Communal Intellectual Property Rights in North Sulawesi. Data analysis uses the content analysis method for primary and secondary legal materials, while data obtained through interviews uses qualitative data analysis. The results of the research show that the regulation of Communal Intellectual Property includes several regulations, namely Law of the Republic of Indonesia Number 11 of 2013 concerning Ratification of the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Haring of Benefits Arising from Their Utilization to the Convention on Biological Diversity, Law- Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright, Law of the Republic of Indonesia Number 20 of 2016 concerning Marks and Geographical Indications. The role of the regional government of North Sulawesi Province and Regency/City in providing protection for Communal IPR by carrying out registration which includes Traditional Cultural Expressions and Traditional Knowledge, while Indications of Origin and Geographical Indications as well as Genetic Resources have not yet been registered. This research concludes the Legal Regulation of Communal Intellectual Property It has not been regulated in a specific regulation but is still spread across several laws and regulations, while the role of Regional Government shows that not all are actively paying attention to protecting Communal IPR, which is measured by the number of Communal IPR registered and those currently in the registration process.